Assessment of the effects of greywater discharge by using streeter-phelps model - Ariffin, Athirah (2019)
Greywater is generated from household activities in bathroom, kitchen and laundry. Pollution of wastewater occurs when the greywater is discharged directly into the stream from the houses and accumulates in the drain. The organic pollutants and suspended particulate matter from greywater may cause depletion of oxygen content in the water which lead to unpleasant odours and increased organic matter degradation time. The aim of this study is to assess the effect of greywater discharged using the Streeter-Phelps model. The first objective of this study to determine the raw greywater characteristics and variations of greywater pollutants loading rate (BOD5). Secondly, the assessment of greywater pollution modelling was measured by using Streeter-Phelps model. The questionnaire were conducted to obtain the household demographic profiles and household activities practice data from respondents. Five sampling points which involve Drain1 to Drain5 for greywater study came from 48 households before mixing with stream. After greywater sampling, hydraulic and physicochemical parameters were measured at intervals from Station0 to Station7 along the stream after mixing with greywater discharge. The results of greywater quality were 172 mg/L for BOD5, 400 mg/L for COD, and 4.5 for pH. The results showed that the highest BOD5 loading rate for daily flow rate was observed at Drain3 with the values of 63 kg/day and 369 m3/day. These drains have a high frequency of household activities and number of occupants leads to high amount of pollutant loading rate produced from greywater drainage. The validity of the simulated DO from Streeter-Phelps model proved that the regression of Thomas slope method indicated a good fitting with laboratory analysis. Furthermore, the curve of the measured and simulated DO showed a gradual increase in the DO movement, indicating a rapid self-purification of the stream. The DO deficit (Dt) and time critical (tc) were 3.54 and 3.80 mg/L and 0.007 per day, respectively, as recorded at the distance of 10 m upstream (Station1) of the discharge point. Findings show that the degradable organic matter and travel time as a critical oxygen deficit point occurred at 10 m upstream as the kinetics of BOD reaction. Hence, the greywater discharge with mixing stream showed no risk of pollution occurrence near the river flow in this study.